2018
DOI: 10.3389/fmicb.2018.00779
|View full text |Cite
|
Sign up to set email alerts
|

Propolis Extract for Onychomycosis Topical Treatment: From Bench to Clinic

Abstract: Onychomycosis is a chronic fungal infection of nails, commonly caused by dermatophyte fungi, primarily species of Trichophyton. Because of the limited drug arsenal available to treat general fungal infections and the frequent failure of onychomycosis treatment, the search for new therapeutic sources is essential, and topical treatment with natural products for onychomycosis has been encouraged. Propolis, an adhesive resinous compound produced by honeybees (Apis mellifera), has shown multiple biological propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 68 publications
2
41
0
7
Order By: Relevance
“…are the main agents responsible for the nail infections [ 13 ]. We propose that this extract may be used as a topical treatment for OM, similar to our findings with propolis extract, another natural compound [ 14 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…are the main agents responsible for the nail infections [ 13 ]. We propose that this extract may be used as a topical treatment for OM, similar to our findings with propolis extract, another natural compound [ 14 ].…”
Section: Discussionsupporting
confidence: 82%
“…The main agents of OM are dermatophyte fungi, from the genus Trichophyton [ 13 ], particularly species of T. rubrum and T. mentagrophytes complexes [ 9 ], including the anthropophilic species T. interdigitale [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Veiga and coworkers showed that propolis, an extract derived from an apiary of hives of honey bees ( Apis mellifera L.) has shown promise in the treatment of onychomycosis [ 164 ]. This natural product is able to penetrate the nail without cytotoxicity and has good antifungal activity [ 165 ]. The authors used propolis with success in the treatment of three elderly patients with onychomycosis.…”
Section: Current and Future Developmentsmentioning
confidence: 99%
“…Recent pilot studies suggest potential for other natural compounds as therapeutic options for onychomycosis. For example, propolis, an adhesive resinous compound produced by honeybees to seal and protect their hives from pathogenic agents, exhibits significant antifungal and anti-biofilm activities in vitro [ 31 ]. A pilot study assessing treatment of onychomycosis with topical ethanol propolis extract for six months showed complete mycological and clinical cure in 56.3% ( n = 16), with no adverse events reported [ 31 ].…”
Section: Natural Therapiesmentioning
confidence: 99%
“…For example, propolis, an adhesive resinous compound produced by honeybees to seal and protect their hives from pathogenic agents, exhibits significant antifungal and anti-biofilm activities in vitro [ 31 ]. A pilot study assessing treatment of onychomycosis with topical ethanol propolis extract for six months showed complete mycological and clinical cure in 56.3% ( n = 16), with no adverse events reported [ 31 ]. The over-the-counter topical cough suppressant Vicks VapoRub ® also showed some effectiveness against onychomycosis in a small-scale uncontrolled pilot study ( n = 18; mycological cure rate 27.8%; partial/complete clinical cure rate 55.6%/27.8%) [ 32 ].…”
Section: Natural Therapiesmentioning
confidence: 99%